DESIGN OF MUARA ANGKE FISHING PORT FACILITIES - Kamajaya, Murti
Fishery Port is a place consisting of land and water whose activities are fishing business used as a place for fishing boats to dock, anchor and/or load and unload fish equipped with shipping safety facilities and fishery support activities. Muara Angke Port is in North Jakarta and is classified as PPN. The availability of adequate facilities is expected to be able to support port operational activities in the range of 2023 to 2043. The facilities to be provided will include basic and functional facilities. All facility designs are based on the flow of fish in the port in the plan year. The port will be arranged with a length of 200 m and a width of 17 m. The wharf will be equipped with a trestle with a length of 40 m and a width of 6 m. TPI's facilities will be designed with steel while other facilities will be designed with concrete. The port will also be designed operationally, which means that vehicles will be designed to operate at the port, pavement, and port parking.